Предмет: Алгебра,
автор: Timon230
решите уравнение через дискриминант
Приложения:
![](https://files.topotvet.com/i/b2a/b2af4bfcb9b9d33cf43cbbc9a8a96a0c.jpg)
Ответы
Автор ответа:
0
3)остальное не знаю
Автор ответа:
0
1) D=(-(-3√2))²-4×1×4=(√9×2)²-16=18-16=2
x1=(-(-3√2)-√2)/2×1=(3√2-√2)/2=(2√2)/2=√2
x2=(-(-3√2)+√2)/2×1=(3√2+√2)/2=(4√2)/2=2√2
2) x²-3x-(5+√7)=0
(5+√7)=5+2,6457~5+2,646=7,646~7,65
x²-3x-7,65=0
D=(-(-3))²-4×1×(-7,65)=9+30,6=39,6
x1=(-(-3)-√39,6)/2×1=(3-6,29)/2=(-3,29)/2=-1,645
x2=(-(-3)+√39,6)/2×1=(3+6,29)/2=9,29/2=4,645
3) x²+2(1+√8)x+8√2=0
x²+2×2,83x+11,31=0
x²+5,66x+11,31=0
D=(-5,66)²-4×1×11,31=32,03-45,24=-13,21
так как D<0, то нет решения уравнения.
x1=(-(-3√2)-√2)/2×1=(3√2-√2)/2=(2√2)/2=√2
x2=(-(-3√2)+√2)/2×1=(3√2+√2)/2=(4√2)/2=2√2
2) x²-3x-(5+√7)=0
(5+√7)=5+2,6457~5+2,646=7,646~7,65
x²-3x-7,65=0
D=(-(-3))²-4×1×(-7,65)=9+30,6=39,6
x1=(-(-3)-√39,6)/2×1=(3-6,29)/2=(-3,29)/2=-1,645
x2=(-(-3)+√39,6)/2×1=(3+6,29)/2=9,29/2=4,645
3) x²+2(1+√8)x+8√2=0
x²+2×2,83x+11,31=0
x²+5,66x+11,31=0
D=(-5,66)²-4×1×11,31=32,03-45,24=-13,21
так как D<0, то нет решения уравнения.
Похожие вопросы
Предмет: Литература,
автор: Pro100vEh
Предмет: Физика,
автор: boyka82
Предмет: Алгебра,
автор: dkyleshov75
Предмет: Биология,
автор: Lero4ka29
Предмет: Литература,
автор: burlachkoo